Pengembangan Buku Pedoman Man To Man Defense Bola Basket Untuk Pelatih - Baskoro Nugroho Putro; Ardhi Kurniawan; Muhammad Soleh Fudin (Journal Sport Area, 2018)
In man to man defense, there are some principles included such as rotation, help and recover. Defense is the vision of whole field and position arrangement between player and a ball which is an important basic to support the most of basketball defense phylosophy. Well-comprehension of man to man defense will increase team playing quality. The coach that is responsible for players’ understanding must be able to explain and apply man to man defense properly. In order to make every coach has good perspective as suitable as man to man principles, it is needed a certain media that can be utilized to learn about it. Media is expected to have important role to strengthen academic performance. This research aimed to develop a media that can be used by every coach as guidance to learn man to man defense. This media can be used as guidance for uncertified coaches or as reminding for certified coaches and the ex-certified coaches. There were 21 Basketball coaches in Trenggalek Regency which included as samples of this research.The data were collected by opened-questionnaire in preliminary research, semi-opened questionnaire in try out by the expert and closed-questionnaire in field try out. The couches agreed on this guidance book development because there is no special book for man to man defense. This media was developed by ADDIE model and helped by two experts to increase the quality of product that one expert concerned on media and another concerned on content. Based on the experts’ validation and try out, this media is acceptable to use.